Phase Development and Dielectric, Ferroelectric and Piezoelectric Properties of Pb(Mg1/3Nb2/3)0.9Ti0.1O3-Bi0.5(Na0.74K0.26)0.5TiO3Ceramics - Methee Promsawat (2018)
© 2015 Taylor & Francis Group, LLC. In this work, the relationships between phase development and the properties of a new relaxor based ferroelectric (1-x)Pb(Mg 1/3 Nb 2/3 ) 0.9 Ti 0.1 O 3 -xBi 0.5 (Na 0.74 K 0.26 ) 0.5 TiO 3 ceramics (when x = 0.0, 0.1, 0.3, 0.5, 0.7, 0.9 and 1.0 mole fraction) was studied. The pseudo-cubic structure was observed in the ceramics with x ≤ 0.7 mole fraction. The rhombohedral and tetragonal phases were found to coexist when x increased to 0.9, which transformed into the single tetragonal phase when x increased to 1.0. The dielectric constant measured at room temperature decreased with increasing x. The remnant polarization and piezoelectric constant of the ceramics significantly increased when x increased to 0.9 and 1.0.